PERAN PSIKOLOGI PERKEMBANGAN DALAM DUNIA PENDIDIKAN ANAK USIA DINI DAN KAITANNYA DENGAN PENDIDIKAN KRISTEN - Pardamean Sianturi, Novita; Maniwu, Dohana Sisilia; Muliku, Efron (PT. Giat Konseling Nusantara, 2024)
The role of developmental psychology is very important in early childhood education, because understanding the stages of child development helps educators in designing appropriate and effective curricula. This research examines this role by showing how the principles of developmental psychology can be applied in the context of early childhood education. Apart from that, this research examines the relationship between developmental psychology and Christian education, which emphasizes spiritual and moral values in the care and education of children. This research also examines the problems that occur in early childhood and looks at what factors cause these problems to occur and provide general treatment. By combining developmental theory and Christian education, this research aims to provide insight into the role of developmental psychology in early childhood education which supports children's cognitive and emotional development and shapes their character and morals in relation to Christian education. This research method uses a descriptive qualitative method, with data collection in the form of interview and observation techniques through several questions given, as well as observations made. It is hoped that the results of this research can become a practical guide for educators and parents in implementing educational strategies that are in accordance with child development values and Christian teachings.